Language specificity of lexical-phonological therapy in bilingual aphasia: A clinical and electrophysiological study. Issue 4 (3rd July 2016) - Radman, Narges; Spierer, Lucas; Laganaro, Marina; Annoni, Jean-Marie; Colombo, Françoise
Abstract : Based on findings for overlapping representations of bilingual people's first (L1) and second (L2) languages, unilingual therapies of bilingual aphasia have been proposed to benefit the untrained language. However, the generalisation patterns of intra- and cross-language and phonological therapy and their neural bases remain unclear. We tested whether the effects of an intensive lexical-phonological training (LPT) in L2 transferred to L1 word production in a Persian-French bilingual stroke patient with Broca's aphasia. Language performance was assessed using the Bilingual Aphasia Test, a 144-item picture naming (PN) task and a word–picture verification (WPV) task. Electroencephalography (EEG) was recorded during PN and WPV in both languages before and after an LPT in French on a wordlist from the PN task. After the therapy, naming improved only for the treated L2 items. The naming performance improved neither in the untrained L2 items nor in the corresponding items in L1. EEG analyses revealed a Language x Session topographic interaction at 540 ms post-stimulus, driven by a modification of the electrophysiological response to the treated L2 but not L1 items. These results indicate that LPT modified the brain networks engaged in the phonological-phonetic processing during naming only in the trained language for the trained items.